ChemInform Abstract: Eco‐Friendly Approach to Tetrasubstituted Diazodihydrofuranones: Valuable Precursors of Oxetane Derivatives and Other Heterocyclic Compounds. Issue 38 (3rd September 2015) - Galkina, Olesia S.; Maas, Gerhard; Rodina, Liudmila L.; Nikolaev, Valerij A.
Abstract The developed reaction sequence provides 2, 2, 5, 5‐tetraalkyl, 2, 2, 5, 5‐tetraaryl as well as regioisomeric 2, 2‐diaryl‐5, 5‐dimethyl and 2, 2‐dimethyl‐5, 5‐diaryldiazofuranones.